Anthocyanins from pomegranate (Punica granatum L.) - Cabrita, Luís (2002)
The anthocyanin contents in the fruits from three cultivars of Punica granatum L. (asseria, mollar and negral) was studied. Six anthocyanins were isolated from the red seeds of pomegranate fruits using a combination of Sephadex LH-20 column chromatography and reverse-phase semi-preparative HPLC. On the basis of chromatographic and spectroscopic techniques, they were identified as the 3-monoglucosides and 3,5-diglucosides of delphinidin, cyanidin and pelargonidin. Total anthocyanin content in fruits of the different cultivars varied in order mollar > negral > asseria. The relative order of aglycone occurrence was cyanidin > delphinidin >> pelargonidin. The 3-monoglucoside and 3,5-diglucoside anthocyanin derivatives occurred in similar amounts. The asseria cultivar was distinct in that it showed to contain more 3,5-diglucosides than 3-monoglucosides. The anthocyanin extracts from fruits of Punica granatum L. could be a suitable source of natural food colorants.